Application of Criminal Sanctions Against Actors of Narcotics Crime Category I in the Form of Possession of Marijuana Fields - Suyatin Suyatin; Abustan Abustan (Budapest International Research and Critics University, 2021)
This study analyzes the efforts to eradicate narcotics criminals carried out by law enforcement officers against the existence of marijuana fields and the cultivation of cannabis plants in the community. This paper uses normative legal research. The research approach used by the researcher is the statutory approach and the conceptual approach. The technique used to analyze the data is descriptive qualitative in line with the research method applied by the researcher. Efforts to eradicate narcotics crimes carried out by law enforcement officers are through penal and non-penal channels. The corrective route is understood through the procedures of the criminal justice system, while the non-penal course involves the community. Article 104 of Law Number 35 of 2009 concerning Narcotics states that the community has the amplest opportunity to prevent and eradicate abuse and illicit trafficking of narcotics and narcotic precursors. Furthermore, Article 105 says that the community has rights and responsibilities to prevent and eliminate abuse and illegal trafficking of drugs and narcotic precursors.